Geometry-based Assurance of Directional Solidification for Complex Topology-optimized Castings using the Medial Axis Transform. (November 2022) - Erber, Maximilian; Rosnitschek, Tobias; Hartmann, Christoph; Alber-Laukant, Bettina; Tremmel, Stephan; Volk, Wolfram
Abstract: Using structural optimization is ideal for the development of complex aluminum cast parts, due to the high degree of design freedom. Various casting processes exist for production, and these differ in their boundary conditions and process restrictions. The resulting geometric restrictions have so far only been taken into account to a limited extent in structural optimization. Hence, there is a desire to determine simple process restrictions that can be taken into account to generate component geometries that are as light as possible but can still be produced by casting. This paper addresses the automated validation and optimization of directional solidification for topology-optimized geometries for castings. For the parametric description of the component volume, the medial axis transform (MAT) method is chosen. This approach allows a subsequent evaluation and optimization by methods of graph theory and feedback into an adapted surface file. The optimization results are finally evaluated by a process simulation using the finite volume method. Highlights: An approach for fast geometric adaption for integrating the production limitations in the topology optimization. This method allows the automatic reduction of casting defects of complex components by ensuring a directional solidification without a casting process simulation. The optimization is achieved by using a mesh-based method of the medial axis transform.